2018
DOI: 10.1007/s10903-018-0705-x
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Hepatitis B Virus Screening, Vaccination, and Linkage to Care Among Newly Arrived Refugees in Four States, 2009–2011

Abstract: Many U.S.-bound refugees originate from countries with intermediate or high hepatitis B virus (HBV) infection prevalence and have risk for severe liver disease. We evaluated HBV screening and vaccination of newly arrived refugees in four states to identify program improvement opportunities. Data on HBV testing at domestic health assessments (1/1/2009-12/31/2011) were abstracted from state refugee health surveillance systems. Logistic regression identified correlates of infection. Over 95% of adults aged ≥19 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 25 publications
2
21
0
Order By: Relevance
“…To our knowledge, this is the first analysis of a large, multisite data set to assess screening coverage resulting from the domestic medical examination recommended for newly arrived refugees and other eligible visa holders in the US. Our data are consistent with prior studies that have reported high screening coverage for TB (93%) [16] and HBV (92.5%) during the domestic medical examination [11,13,16]. Compared with two studies reporting screening coverage for intestinal parasites among refugees in Minnesota (64%-80%) [16,17], our analysis found a lower screening coverage among refugees (50.2%).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…To our knowledge, this is the first analysis of a large, multisite data set to assess screening coverage resulting from the domestic medical examination recommended for newly arrived refugees and other eligible visa holders in the US. Our data are consistent with prior studies that have reported high screening coverage for TB (93%) [16] and HBV (92.5%) during the domestic medical examination [11,13,16]. Compared with two studies reporting screening coverage for intestinal parasites among refugees in Minnesota (64%-80%) [16,17], our analysis found a lower screening coverage among refugees (50.2%).…”
Section: Discussionsupporting
confidence: 90%
“…In a review of the literature, we found that most analyses based on domestic medical examination data occur at the clinic, state, or local levels [10] and may not represent all recipients of refugee health program services, given the heterogeneity of these populations. Where domestic examination data are pooled across states or sites, analyses are generally limited to a particular condition (e.g., hepatitis B, lead) or population (e.g., children) [11][12][13][14]. Finally, we identified few analyses that reported the proportion of persons screened by condition during the domestic medical examination [10][11][12], which, to our knowledge, prevents assessment of the impact of the domestic examination on screening coverage.…”
Section: Introductionmentioning
confidence: 99%
“…HBV-infected patients require regular monitoring for both infection and sequelae. Several studies have evaluated initial linkage to HBV care for both refugee and nonrefugee immigrant populations (4)(5)(6)(7)(8)(9), but none contained standardized definitions for either linkage to or long-term retention in care for chronic HBV-infected refugees. To assess chronic HBV care, three urban sites that perform refugee domestic medical examinations and provide primary care collaborated in a quality improvement evaluation.…”
mentioning
confidence: 99%
“…For hepatitis B, hepatitis B virus surface antigen (HBsAg), antibody to hepatitis B core antigen (anti-HBc), and antibody to hepatitis B surface antigen (anti-HBs) results were used to categorize a person's hepatitis B virus (HBV) infection status. Status was categorized as susceptible (HBsAg, anti-HBc, and anti-HBs all negative), uninfected/susceptibility unknown (HBsAg negative, anti-HBc and anti-HBs unknown), infected (HBsAg positive), immune through natural infection (HBsAg negative, anti-HBc positive, and anti-HBs positive), immune through hepatitis B (hepB) vaccination (HBsAg negative, anti-HBc negative, and anti-HBs positive), and immune but not specified (HBsAg negative, anti-HBs positive, and anti-HBc unknown) [16]. During the time of data collection, CDC guidelines recommended screening blood for lead in children ages 6 months to 16 years, with EBLL defined as �5 mcg/dL [17].…”
Section: Analysis Population and Data Collectionmentioning
confidence: 99%